Critical Infrastructure Designation in European Union Countries: Implementation of Systems Approach - Novotny, Petr; Markuci, Jiri; Rehak, David; Almarzouqi, Ibrahim; Janusova, Lucia (Communications - Scientific Letters of the University of Zilina, 2016)
The contribution deals with the issue of designating critical infrastructure elements in European Union Countries. Based on approach analysis in selected countries, where sufficient attention is paid to the area of critical infrastructure, the aim of the article is to propose a systems approach to critical infrastructure designation. The aim is determined by the fact that a significant number of EU countries do not currently apply the systems approach and designating of elements is realized via sectors approach, i.e. without taking possible bonds with other sectors into consideration. Therefore, using the systems approach may be a solution to realizing further necessary steps in the area of critical infrastructure protection, for example complementing the issue of resilience and modelling dependences in the area of critical infrastructure.
Keywords: critical infrastructure; designation; systems approach; European Union